Pharmacoeconomic analysis of using biological agents in the treatment of rheumatoid arthritis - I. I. Dyakov; D. V. Goryachev (Современная ревматология)
By taking into account the fact that there are a few alternative biological agents for the treatment of rheumatoid arthritis (RA), the cost of an annual therapy cycle using the agents is greater than that of high-technology surgical interventions, and a pharmacoeconomic study substantiating the optimal choice of a specific drug has been conducted. The pharmacoeconomic analysis has indicated the use of the biological agents etanercept (ETC) can decrease the cost of an annual therapy cycle for each patient with RA by an average of 84,764–481,622 rubles and considerably increase the number of patients receiving the current therapy without allocating additional resources. Switching 100 patents with RA to a treatment regimen including ETC enables 14–78% of the patient with this condition to be additionally treated within the framework of the same budget. The given results with regard to the data that there are significant differences in the efficacy and safety of biological agents usedto treat RA (National and EULAR guidelines for the treatment of RA, a number of meta-analyses of randomized controlled clinical trials) may conclude that the treatment regimen incorporating ETC is most preferential. The cost-effectiveness analysis based on the single meta-analysis proposed by G.J. Bergman et al., which had demonstrated differences in the efficacy of biological agents, also yielded the similar results. In this case, the administration of ETC is also more preferential because it can minimize expenditures of the health care system to achieve ACR20 and ACR50 responses. This advantage of ETC will cause the highest reduction in the number of hospital admissions, social benefits, and other expenses associated with the management of patients with RA. The authors are aware of the disadvantages of the performed trial, which cannot fully interpret uniquely the findings: the results of meta-analyses have limitations due to its low sensitivity in assessing the differences between the drugs; the virtually complete absence of published data on the direct comparison of the drugs, by employing sufficient patient samples, makes it necessary to use the data of the meta-analyses and to state that biological agents have similar efficacy and safety within the clinically permissible limit to recognize their equivalence; the trial has considered only an annual perspective to use the agents without regard for their therapy discontinuation rate and remission rate that requires that treatment should not be continued.